The lived experience of liver transplant recipients in New Zealand - Wainwright, Bethli (Auckland University of Technology, 2011)
This thesis reports on phenomenological research into the lived experience of liver transplant recipients in New Zealand in 17 qualitative interviews, and a qualitative survey of 49 liver transplant recipients across New Zealand. A new survey tool was developed for this work. A brief background to liver transplantation in New Zealand and internationally is provided. The perspectives of liver transplant recipients are then shown in relation to their experiences on becoming unwell, waiting for transplantation, in Intensive Care and the ward, and their way of coping with a donor liver from another human being. The thesis concludes with recommendations for immediate implementation by the New Zealand Liver Transplantation Unit. Appendices include survey responses on an Excel spread sheet and a database of references on liver transplantation to assist further research in this field.
Keywords: Quality of life; Well-being; Organ transplantation; End-stage liver disease; Immunosuppression; Care giver support; Accepting a donor liver; Phenomenology; Qualitative research